Aspiracje edukacyjne rodziców i dzieci a osiągnięcia szkolne - Kozłowski , Waldemar; Matczak , Ewa (Studia Edukacyjne, 2018)
Numerous studies have found an association of educational aspirations of parents and children with their school achievement. The study verifies these relationships for about 5,000 people, a representative sample of parents and their children-primary school students. Three aspects of aspirations were taken into account: the maximum (desired), the feasible (expected) and the lowest acceptable. Expected aspirations of parents are mostly related to the achievements of children; students’ achievements are associated with both their feasible and maximum aspirations. There was a significant relationship between aspirations of parents and children and a strong correlation between parental aspirations and their level of education.